2002
DOI: 10.1007/s00420-002-0344-2
|View full text |Cite
|
Sign up to set email alerts
|

Possibilities to control the health risk of petrochemical workers

Abstract: The decrease of GPx and GSH and the increase of the MDA levels give evidence of misbalance in the antioxidant status. The decreased values of MDA and the increased GPx activity and GSH concentrations at the second examination proved the positive effect of the treatment. The strengthened antioxidant potential of workers exposed to a mixture of hydrocarbons confirmed the possibilities that the exposure-related health risk can be controlled and the adverse effects prevented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
16
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 10 publications
7
16
0
1
Order By: Relevance
“…The T-SOD activities and GSH levels were significantly lower in refueling workers than in office workers, whereas the MDA and 8-OHdG levels showed the opposite trends. Our results are also supported by investigations on oxidative stress detected in various occupational exposures [31,32,33]. Comet parameters were used to study DNA damage, and significant increases in TM and OTM were noted in refueling workers.…”
Section: Discussionsupporting
confidence: 87%
“…The T-SOD activities and GSH levels were significantly lower in refueling workers than in office workers, whereas the MDA and 8-OHdG levels showed the opposite trends. Our results are also supported by investigations on oxidative stress detected in various occupational exposures [31,32,33]. Comet parameters were used to study DNA damage, and significant increases in TM and OTM were noted in refueling workers.…”
Section: Discussionsupporting
confidence: 87%
“…This study showed high statistical significant difference among exposed group compared to control group regarding the level Malondialdehyde (MDA) which was higher among exposed. This is in agreement with other studies which illustrated that Benzene exposure has been associated with increases in the overall formation of MDA (21,22) , also this study is consistent with other studies which found a significant increase in the level of MDA in petrol station workers compared to their control group (6,19,(23)(24)(25) . In addition, a study by Abdallah et al (26) also showed increased level of MDA among shoe makers exposed to petroleum products.…”
Section: Discussionsupporting
confidence: 83%
“…Present findings showed high statistical significant difference among benzene exposed group compared to control group regarding the level of MDA or lipid 566 peroxidation. This is in agreement with other studies and also with our previous finding of genotoxic effect which illustrated that benzene exposure has been associated with elevated level of MDA (Georgieva et al, 2002;Ragia et al, 2014;Roy and Pillai, 2015). Results from the present study demonstrate that the antioxidative enzymes like SOD, catalase, GSH and GPx activity was lowered down due to benzene treatment which is supported by the findings of Ragia et al (2014) and Khadiga et al (2011).…”
Section: Discussion:-supporting
confidence: 82%